Higgs Bosons of Gauge-Extended Supersymmetry at the Lhc - Sert, Hale; Demir, Durmuş Ali (Izmir Institute of Technology, 2010)
This thesis work is devoted to a detailed phenomenological analysis of the Higgs sector of gauge-extended supersymmetry in light of the most recent experimental bounds. Such extra gauge symmetries, obtained by adding an extra Abelian symmetry U(1). to the gauge structure of the Standard Model (SM) and Minimal Supersymmetric Standard Model (MSSM) which have the same gauge structure, are urged by the . problem of the MSSM, and they also arise frequently in low-energy supersymmetric models stemming from GUTs and strings. We analyze the Higgs boson masses and their dependencies on various model parameters. In particular, we compute masses of all the Higgs bosons, and confront the mass of the lightest one with the LEP and Tevatron experiments. Then we indicate the restrictions from LEP and Tevatron bounds on the masses and remaining model parameters. We analyze correlations among various model parameters, and determine excluded regions by both scanning the parameter space and examining certain likely parameter values. Furthermore, we make educated projections for LHC measurements in light of the LEP and Tevatron restrictions on the parameter space. As a result of this thesis work we find that .-problem motivated generic lowenergy U(1). model yields lightest Higgs masses as large as . 200 GeV, and violates the Tevatron bounds for certain ranges of parameters. However, we find that U(1). model stemming from E(6) breaking elevate Higgs boson mass into Tevatron.s forbidden band when U(1). gauge coupling takes larger values than the one corresponding to one-step GUT breaking. We also obtain that the Tevatron bounds put strong restrictions on certain parameters of the U(1). model and they lead to determinations of certain parameter ranges before the LHC measurements.
Thesis (Master)--Izmir Institute of Technology, Physics, Izmir, 2010
Includes bibliographical references (leaves: 72-75)
Text in English; Abstract: Turkish and English
ix, 79 leaves
Keywords: Supersymmetry; Higss bosons